Respostas

  • Ind
  • Ambicioso
2014-01-08T11:06:13-02:00
Função Quadrática : f(x) = ax² + bx + c
f(0) = a.0² + b.0 + c = 1 
c = 1

f(2) = 5 
a.(2)² + b.(2) + 1 = 5 
4a + 2b = 5 - 1 
4a + 2b = 4 (podemos simplificar por 2)
2a + b = 2 (Equação I)

f(3) = 12
a.(3)² + b.(3) + 1 = 12 
9a + 3b = 12 - 1
9a + 3b = 11 (Equação II)

Sistema com as equações I e II:
 \left \{ {{2a + b = 2} \atop {9a + 3b = 11}} \right.

multiplique a I por - 3 

 \left \{ {{-6a - 3b =  - 6} \atop {9a + 3b = 11}} \right.

3a + 0b =  5 
a =  \frac{5}{3}

2a + b = 2
2. \frac{5}{3} + b = 2

b = 2 -  \frac{10}{3}

b =  \frac{6 - 10}{3}

b = -  \frac{4}{3}


f(x) =  \frac{5}{3}  x^{2} -  \frac{4}{3}x + 1

Bons estudos... 



2 1 2